Does the Motor Cortex Want the Full Story? The Influence of Sentence Context on Corticospinal Excitability in Action Language Processing. (1st December 2022) - Dupont, W.; Papaxanthis, C.; Lebon, F.; Madden-Lombardi, C.
Highlights: We studied the effects of action words and sentence context on motor activity. Corticospinal excitability is modulated by the presence of manual action verbs. Context helps eliminate residual motor activation when no manual action is present. Abstract: The reading of action verbs has been shown to activate motor areas, whereby sentence context may serve to either globally strengthen this activation or to selectively sharpen it. To investigate this issue, we manipulated the presence of manual actions and sentence context, assessing the level of corticospinal excitability by means of transcranial magnetic stimulation. We hypothesized that context would serve to sharpen the neural representation of the described actions in the motor cortex, reflected in context-specific modulation of corticospinal excitability. Participants silently read manual action verbs and non-manual verbs, preceded by a full sentence (rich context) or not (minimal context). Transcranial magnetic stimulation pulses were delivered at rest or shortly after verb presentation. The coil was positioned over the cortical representation of the right first dorsal interosseous (pointer finger). We observed a general increase of corticospinal excitability while reading both manual action and non-manual verbs in minimal context, whereas the modulation was action-specific in rich context: corticospinal excitability increased while reading manual verbs, but did not differ from baseline for non-manual verbs. These findings suggest that sentence context sharpens motor representations, activating the motor cortex when relevant and eliminating any residual motor activation when no action is present.